The Emigration of German-Speaking Economists after 1933 - Scherer, F. M (Journal of Economic Literature, 2000)
Economists were among the many scholars uprooted following Hitler's rise to power in 1933. This article reviews a series of books edited by Harald Hagemann and others which provide extensive biographical information on 314 German-speaking economists whose professional opportunities were shattered by Nazi policies. It evaluates the impact of the massive emigration on economic research and teaching in Germany and Austria and in the nations to which most of the economists emigrated. An analysis of 1966-70 data reveals that the emigres' cited publication counts were equivalent to the citations of three leading U.S. economics departments.